Clinical and genetic features of a Noonan syndrome with a de novo MAP2K1 mutation: A case report - Díaz-Quiquia, Vasti Evelyn (2022)
Background: Noonan syndrome is a genetic disorder mostly related to PTPN11 gene mutation. Report Case: Newborn male of 34 weeks of gestational age with obstetric ultrasounds showing cystic hygroma, bilateral renal hydronephrosis, and polyhydramnios. At born, he presented nuchal edema, wide nose, low-set ears, and right cryptorchidism. Additionally, he presented atrial septum defect, absence of inferior vena cava, mild pulmonary hypertension, persistent ductus arteriosus, and respiratory distress. The result of the 14-gene panel analysis showed a MAP2K1 gene mutation and a variation of uncertain significance in the CBL gene, confirming the diagnosis of PTPN11-negative Noonan syndrome. During the follow-up, he was additionally diagnosed with blepharoptosis of left eye and gastroesophageal reflux disease. Conclusion: This report highlights the wide variety of phenotypical characteristics in a Noonan syndrome patient, which was suspected upon birth and developed during the follow-up.